Violência obstétrica e racismo: uma revisão integrativa da literatura - Viana, Taís Souza (Universidade Federal do Tocantins, 2024)
This article aims to analyze the relationship between obstetric violence and racism in Brazilian scientific production, highlighting the role of structural racism in the occurrence of this violence and the suffering of black women. Additionally, the study seeks to investigate how Psychology has positioned itself in this debate. Using the integrative literature review methodology, six studies obtained from the Virtual Health Library (BVS) and the Scientific Electronic Library Online (SciELO) were analyzed. From this analysis, three thematic categories were identified: Obstetric violence as a practice of rights violation and its effects, (In)Definitions of Racism, and Associations between obstetric violence and racism. The results indicated that the analyzed productions are not centered in the field of Psychology, emphasizing the need to expand the debate in this area. Furthermore, it was observed that definitions of racism are not always explored or clearly defined in the literature, which can hinder the understanding and identification of this social phenomenon. Regarding the association between obstetric violence and racism, topics such as the resistance of black women to pain, institutional racism, and reproductive justice were discussed.